Integrated utilization of maize residues and kernels through silage and flour production - Yayat Hidayat; Anca Awal Sembada; Alfi Rumidatul; Marsinah; Tuti Juhaeti; Dedi Ruswandi (CV. Literasi Indonesia, 2026)
Laju Village, Langgudu District, Bima Regency, is one of the major maize-producing areas in West Nusa Tenggara, Indonesia. However, maize harvest residues, including stalks, leaves, and husks, remain largely underutilized, while dried maize kernels are generally sold without further processing, resulting in relatively low economic returns for farmers. This community service program aimed to improve the income and self-reliance of maize farmers through the implementation of two appropriate technologies: the production of silage from maize harvest residues as livestock feed and the processing of maize kernels into maize flour as a value-added product. The program was implemented through four stages: an initial survey and socialization, theoretical and hands-on training on silage and maize flour production, one month of technical mentoring, and program evaluation using pre-test and post-test assessments. The program involved members of a maize farmer group in Laju Village. The results showed a substantial improvement in participants' knowledge and technical skills, with an average knowledge increase of 89.6% following the training. Participants successfully produced high-quality silage (pH 4.2) and maize flour with a yield of 82.5%, demonstrating the feasibility of both technologies at the community level. The integration of these two technologies increased the economic value of both maize harvest residues and maize kernels while reducing dependence on conventional livestock feed and the sale of unprocessed maize. Overall, this dual-technology approach proved to be an effective community empowerment model based on local agricultural resources, contributing to improved farmer livelihoods and promoting sustainable rural economic development.